The Design of Experiential Services with Acclimation and Memory Decay: Optimal Sequence and Duration - Das Gupta, Aparupa; Karmarkar, Uday S.; Roels, Guillaume (Management Science, 2016)
For many consumer-intensive (i.e., business-to-consumer) services, delivering memorable customer experiences is a source of competitive advantage. Yet there are few guidelines available for designing service encounters with a focus on customer satisfaction. In this paper, we show how experiential services should be sequenced and timed to maximize the satisfaction of customers who are subject to memory decay and acclimation. We find that memory decay favors positioning the highest service level near the end, whereas acclimation favors maximizing the gradient of service level. Together, they maximize the gradient of service level near the end. Although memory decay and acclimation lead to the same design individually, they can act as opposing forces when considered jointly. Overall, our analysis suggests that short experiences should have activities scheduled as a crescendo and duration allocated primarily to the activities with the highest service levels, whereas long experiences should have activities scheduled in a U-shaped fashion and duration allocated primarily to activities with the lowest service level so as to ensure a steep gradient at the end. This paper was accepted by Serguei Netessine, operations management.